2015
DOI: 10.5539/gjhs.v8n7p245
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Complications of Uterine Artery Embolization in Symptomatic Uterine Fibroids

Abstract: We decided to evaluate the efficacy and complications of uterine artery embolization (UAE) in patients with symptomatic uterine fibroids. Sixty-five premenopausal patients, without considering the fibroids size and its location, were treated by bilateral UAE. At baseline and after 3, 6, and 12 months MRI was obtained to determine the uterine length and fibroid diameter. In addition, symptoms of the patients were documented at these follow-up schedules. UAE was successful in 62 (95.4%) cases. Complete infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…The major adverse effects (Class C&D) were only seen in 104 patients, which account for 0.79% (104/13,170). The rate of major adverse effects was lower than that of other treatment modalities [14][15][16][17]. Table 3 showed that the common minor adverse effects observed in this study were mild lower abdominal pain, sacrococcyygeal pain, and abnormal vaginal discharge.…”
Section: Discussionmentioning
confidence: 58%
“…The major adverse effects (Class C&D) were only seen in 104 patients, which account for 0.79% (104/13,170). The rate of major adverse effects was lower than that of other treatment modalities [14][15][16][17]. Table 3 showed that the common minor adverse effects observed in this study were mild lower abdominal pain, sacrococcyygeal pain, and abnormal vaginal discharge.…”
Section: Discussionmentioning
confidence: 58%
“…Median takip süresi 7 yıl olan bir çalışmada, UAE sonrası hastaların ağrı yakınmasındaki düzelme %78,9 olarak bulunmuştur (19) . UAE işlemi sonrası ağrı ve kanama yakınmasındaki belirgin düzelme, hastaların yaşam kalitelerine olumlu yansımaktadır (20) . Sonuç olarak, 1.278 hastanın 3 yıl takip edildiği çok merkezli bir çalışmada, hastalarda semptom skorunun %85,3 iyileşme ile uzun dönemde sürdürülebilir bir iyileşme olduğunu ortaya koymuştur (12) .…”
Section: Discussionunclassified
“…Performing cryoablation several months post-embolization allows for adequate tumor shrinkage, as well as recovery of renal function [ 10 ]. Similarly, to achieve adequate post-bland embolization shrinkage for other tumors such as uterine fibroids, two months between procedures is usually adequate to achieve the desired size reduction [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bland arterial embolization is currently used to debulk tumors such as uterine fibroids as well as hyperplastic tissue such as that found in benign prostatic hyperplasia [ 4 - 5 ]. This is accomplished using fluoroscopy by selectively embolizing the feeding vessels of these structures which results in ischemia followed by shrinkage.…”
Section: Introductionmentioning
confidence: 99%